King Leopold II's Last Laugh: The Evolution of Mgr. Augouard's Attitudes towards the Congo Free State (1890-1908) - Lopes Pereira, Jairzinho (The catholic historical review, 2019)
This article addresses the evolution of the relationship between Bishop Prosper Augouard and King Leopold II's Congo Free State from the closure of the Brussels Anti-Slavery Conference to the termination of the regime in 1908. Augouard's public denunciations in October 1894, of State-sanctioned/sponsored slavery and other abuses publicly attacked the prevalent collaborationist behaviors of the Catholic Church in its dealings with the European colonial regimes. With no support and forced into silence, Augouard became an easy prey to Leopold's vulpine charms. The monarch easily won over the prelate and transformed him into a major asset in the Congo Free State's struggles against the vigorous Congo Reform Movement throughout the 1900s.